2021
DOI: 10.1590/0034-761220200597
|View full text |Cite
|
Sign up to set email alerts
|

Benefícios fiscais e sustentabilidade: um estudo dos municípios catarinenses

Abstract: Resumo A relação entre benefícios fiscais e sustentabilidade não tem sido objeto de muitas pesquisas empíricas, apesar da importância da mensuração e do acompanhamento da efetividade dos gastos tributários. Assim, o objetivo deste artigo é analisar a influência dos benefícios fiscais de ICMS - imposto sobre circulação de mercadorias e prestação de serviços de transporte e de comunicação - na sustentabilidade dos municípios catarinenses. Para tanto, com base num conjunto de dados secundários em painel, coletado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…This result is explained by Na et al (2021) who conclude that tax incentives provided to companies increase their net profit and a consequent immediate improvement in their productivity. Moreover, Lu et al, (2022) and Noja et al, (2020) found a positive and significant bidirectional relationship between sustainability and financial execution.…”
Section: Results Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This result is explained by Na et al (2021) who conclude that tax incentives provided to companies increase their net profit and a consequent immediate improvement in their productivity. Moreover, Lu et al, (2022) and Noja et al, (2020) found a positive and significant bidirectional relationship between sustainability and financial execution.…”
Section: Results Discussionmentioning
confidence: 98%
“…Furthermore, the granting of tax benefits leads to the economic success of companies as it directly affects the direct increase in net profit, by reducing corporate tax costs (Yu et al, 2022;Na et al, 2021). In this context, Lu et al (2022) agree that companies that become more sustainable see their profitability improve.…”
Section: The Strategic Political Vision For Forestry: the Role Of Tax...mentioning
confidence: 99%